Astreintes and Italian Law - Caracciolo, Alessio; Stamerra, Federica; Cesareo, Fabrizio (Civil Procedure Review, 2017)
This essay analyses the transposition path into Italian law of the French measure of astreintes, which are an indirect coercive method aimed to force the debtor to fulfill the obligation. The modern configuration has led to the adoption of judgments such as the one related to the “Case Facebook” (Order of the Court of Reggio Emilia, 15 April 2015), involving the urgency protection provided by art. 700 c.c.p. relatively to the hypothesis of defamation on Facebook or other Social Networking Sites. The astreinte find an equal in the Anglo-Saxon sort, by the contempt of court, and in the German one, through the Zwangsstrafen, which led, after several transposition attempts into national law (among which stands out the “Project Carnelutti” of 1926), to the current forecast referred to art. 614 bis c.c.p., introduced by art. 49 of Law 18 June 2009 n. 69. An application issue of the astreinte in Italy concerns its potential struggle with the internal public order: in Italy, there isn’t any provision of punitive damages outlined in common law systems, so that their transposition would lead to a worsening of the obliged subject’s position, in contrast with the proportionality principle on which is based the compensation statement system. The Italian Supreme Court, by the judgment of 15 April 2015 n. 7283, expresses itself in the opposite direction, stating that “the astreintes provided in other jurisdictions […] are not incompatible with the Italian public policy”. The contemporary Italian law framework, based on the right of “forced execution”, which one can deduct from the art. 24 of the Constitution (which states that all may take legal action for protecting their rights and legitimate interests), is outlined from the Book III, Title IV of the Italian Code of Civil Procedure, indexed “the enforcement of proactive or passive obligations”, Articles 612 to 614 bis c.c.p., where it is possible to involve, from the address of the art. 614 bis c.c.p., the irreplaceable performance, although the same rule has generated several disputes. To underline the value and the transverse projection of the theme, it is proper to highlight the inapplicability of Article 614 bis c.c.p. to individual work disputes listed in art. 409 c.c.p. This exclusion, unjustified and irrational, strongly undermines the principle of equality safeguarded by the art. 3 of the Italian Constitutional Charter, and has given rise to an abundant doctrine that considered art. 614 bis c.c.p., if applied, an extra protection to the right to work contemplated by the art. 4 of the Constitution, and even by art. 18 L. 20 May 1970 n. 300. In this perspective, the art. 614 bis make up a missed opportunity for the code of civil procedure to ensure an executive procedural protection for both parties of the employment contract. The possible reconstructions related to debtor’s indirect coercion shows problematic aspects referring to a potential overlap with ordinary protection instruments provided by Articles 1223 c.c., indexed “compensation of the damage”, and 2932 c.c., indexed “specific execution of the obligation to close a contract”, which, for certain doctrine, would be posed after the means provided by art. 614 bis c.c.p. In this way, the executive safeguards to the damage resulting from the breach would be erroneously duplicated. For certain doctrine, this impasse could be overcome by the second paragraph of this Article, with a factual assessment, carried out by the Court, of the abovementioned principle of irreplaceability, excluding its application to all those obligations deprived of such connotation. Some doctrine opposed another configuration, endorsed by the jurisprudence, which postulates a systematic and teleological interpretation, per which it would be possible to extend such protection independently from a postulate of irreplaceability. In this scenario, the research will, at last, offer an interesting train of thought to the debate on legal affairs in the perspective of a possible future and further reform of the civil execution law, also taking into consideration to transpose into Italian Law an institute inspired by punitive damages and based on the penal principle of rehabilitation function of punishment (rectius, in this case, of execution) referred to art. 27 subparagraph 3 of the Italian Constitution. [...]